Research on Cavitation Regions of Upstream Pumping Mechanical Seal Based on Dynamic Mesh Technique. (5th August 2014) - Chen, Huilong; Wu, Qiangbo; Xu, Cheng; Zuo, Muzi
Abstract : In order to study the cavitation area of the Upstream Pumping Mechanical Seal, three-dimensional microgap inner flow field of the Upstream Pumping Mechanical Seal was simulated with multiphase flow cavitation model and dynamic mesh technique based on hydrodynamic lubrication theory. Furthermore, the simulated result was compared with the experimental data. The results show that the simulated result with the Zwart-Gerber-Belamri cavitation model was much closer to the experimental data. The area of cavitation inception mainly occurred at the concave side of the spiral groove and surrounding region without spiral grooves, which was nearly covered by the inner diameter to roots of grooves; in addition, the region near the surface of the stationary ring was primary cavitation location. The area of cavitation has little relationship with the medium pressure; however, it became larger following increasing rotating speed in the range of researched operating conditions. Moreover the boundary of cavitated area was transformed from smooth to rough, which occurred in similar film thickness. When cavitation number was decreasing, which was conducive to improving the lubrication performance of sealed auxiliary, it made the sealing stability decline.